FEATURES OF PREVENTIVE MEASURES FOR DENTAL PROSTHETICS SUPPORTED BY DENTAL IMPLANTS - O.V. Bida; O.V. Bida (Український стоматологічний альманах)
Main goal increasing the effectiveness of orthopedic treatment and prolonging the period of use of fixed dental prostheses based on dental implants through the use of supportive therapy of peri-implant tissues.